Algerianized French among young people: a lect between plurilingual dynamics and the quest for identity - Mezdaout - Souhila Soltani, Hacina (Romanica Olomucensia, 2022)
This study focuses on plurilingual dynamism in Algerianized French. The interest relates to the formulations of young people, the strategies used by these speakers, and the different languages that form a plurilingualism, but also the linguistic and intercultural ideals and the quest for identity targeted by this public when creating innovative linguistic forms. This is a diachronic qualitative study to see how this lect has evolved, according to an etymological and morphosyntactic analysis. Our corpus includes samples taken from the colonial, post-colonial, and contemporary periods, obtained from testimonies and a collection made in the field. The objective is to trace the imprint of the different languages in the selected lexicon in order to find the different morphemes and their linguistic origins. The analysis of the dynamism of this variant makes it possible to find plurilingualism and pluriculturalism; it is in the components of this lect that the specific characteristics of its culture appear, revealing the relationship between languages and cultures and the identity of the user. In other words, in the lexemes formed, morphemes are linked together which convey cultural traits of the languages of origin. However, they are reconditioned by the speaker's identity, culture, and interpretative vision. It is in this respect that the evolution of the identity of the young Algerian, induced by linguistic creation and innovation, the intertwining of languages, the cohabitation of cultures, and the adjustment of ideas, appears through his/her genius, as well as his/her ability to ensure the continuity of a language considered foreign but which ended up being adapted to the linguistic needs of the time.
Keywords: Algerianized French; lect; plurilingualism; identity; pluricultural; representations